Histopathological Characterization of a Series of Oral Basaloid Squamous Cell Carcinoma. (10th April 2023) - Jain, Neetu; Raut, Toniya; Keshwar, Shashi; Shrestha, Ashish; Jaisani, Mehul Rajesh; Paudel, Deepak
Abstract : Basaloid squamous cell carcinoma (BSCC) is a rare, distinctive, and aggressive variant of squamous cell carcinoma (SCC) primarily seen in the upper aerodigestive tract with epiglottis, soft palate, and base of the tongue being site of high preference in head and neck region. It differs from conventional SCC histologically and immunologically, is most frequently found in males in their sixth and seventh decades, and is frequently linked to alcohol and tobacco use. High stage disease with distant metastases, a high recurrence rate, and a dismal prognosis is how BSCC typically manifests. In the present article, we report four cases of BSCC.